Optimization and Fuel Properties of Water Degummed Linseed Biodiesel from Transesterification Process - Dixit, Sankalp; Dixit, Savita (Challenges and Advances in Chemical Science Vol. 1, 2021)
Biodiesel has become more attractive as an alternative fuel for diesel engine because of its environmental benefits and the fact that it is made from renewable resources such as vegetable oil and animal fats by reacting them with short chain alcohols. The present research work focusses on optimization of water degummed Linseed biodiesel from transesterification process which involves the exchanging of organic group R” of an ester with the organic group of alcohol R’ often catalysed by the addition of an acid or base catalyst. It was found that the maximum recovery of bio- diesel yield was depicted at the optimum operation conditions (0.8% catalyst amount NaOH, reaction time 1 hour and reaction temperature 60°C). The comparison with the fuel properties of conventional diesel, especially with regards to kinematic viscosity and carbon residue, oil needs to purify through the degumming process to remove the gums before use in biodiesel production. The effect of degumming on fuel properties of water degummed Linseed methyl ester and their different diesel blends are discussed in this paper.